Criminal procedure - Samaha, Joel (Wadsworth Cengage Learning, 2012)
Addresses the entire criminal procedure process - from search and seizure to post-conviction sentencing and review by appellate courts - providing case updates and coverage of such key issues as terrorism/homeland security, the USA-PATRIOT Act, searches and seizures, military tribunals, various changes to sentencing guidelines, and more.